Capturing the personal through the lens of the professional: The use of external data sources in autoethnography. Issue 1 (March 2019) - Lee, Catherine
This article shows how external data sources can be utilised in autoethnographic research. Beginning with an account of a critical incident that examines the incompatibility of private and professional identities, I show how, through the collection of data sources, I capture the impact of homophobic and heteronormative discursive practices on health, wellbeing and identity. In the critical incident, I explore how I prospered as a teacher at a British village school for almost 10 years by censoring my sexuality and carefully managing the intersection between my private and professional identities. However, when a malicious and homophobic neighbour and parent of children at the school exposed my sexuality to the Headteacher, I learned the extent to which the rural school community privileged and protected the heteronormative discourse. A poststructuralist theoretical framework underpins this article. My experience of being a subject is understood as the outcome of discursive practices. Sexual identity, teacher identity and autoethnographer identity are understood to be fluid, and constantly produced and reproduced in response to social, cultural and political influences. The article describes how email correspondence, medical records and notes from a course of cognitive behaviour therapy were deployed to augment my personal recollection and give a depth and richness to the narrative. As the critical incident became a police matter, examination takes place of how I sought to obtain and utilise data from the police national computer in the research. Attempts to collect data from the police and Crown Prosecution Service were problematic and provided an unexpected development in the research and offered additional insight into the nature of the British rural community and its police force.